Tahun Sabat dan Tahun Yobel dalam Imamat 25 - Nepho Gerson Laoly (Sekolah Tinggi Teologi Sumatera Utara, 2022)
The Sabbath and Jubilee years already existed in Ancient Israel, first recorded in Leviticus 25. Explanation is needed in distinguishing the Sabbath and Jubilee in Leviticus 25 from the Sabbaths in other texts. The existence of differences in understanding of the Sabbath such as the value of the Sabbath from only one heart to one year needs to be explained clearly. Using the method of exegesis by looking at the grammar and history of Leviticus 25 is useful for entering into the Sabbath and Jubilee Year laws. The Sabbath and Jubilee laws were used as a period of rest for farmland, farmland, property rights, and debt slaves. The word abaton (שַׁבָּת֥וֹן) is a term to stop all activities at a predetermined time. ten years is often achieved as the fiftieth year, but the Jubilee year lasts forty-nine days, in the seventh month only the tenth of the Israelite calendar. AbstrakTahun Sabat dan Tahun Yobel sudah ada di masa Israel Kuno, tercatat pertama sekali di Imamat 25. Penjelasan diperlukan dalam membedakan Sabat dan Yobel di Imamat 25 dengan Sabat di teks lainnya. Adanya perbedaan pemahaman Sabat seperti nilai waktu Sabat mulai hanya satu hati menjadi satu tahun perlu dipaparkan dengan jelas. Menggunakan metode eksegese dengan melihat gramatika dan historis Imamat 25 berguna untuk masuk ke dalam hukum Tahun Sabat dan Tahun Yobel. Hukum Sabat dan Yobel telah digunakan sebagai masa beristirahat bagi tanah pertanian, pengembalian hak kepemilikan tanah, dan pembebasan para budak hutang. Kata Šabaton (שַׁבָּת֥וֹן) menjadi istilah untuk berhenti dari segala aktifitas pada masa yang telah ditentukan. Kendati Yobel sering dipahami sebagai tahun ke lima puluh, tetapi tahun Yobel hanya berlansung selama empat puluh Sembilan hari, pada bulan ketujuh hari ke sepuluh kalender Israel.